Atletas em campos: o movimento Atletas de Cristo como mediador nas relações entre campo esportivo e campo religioso - Ananias, Elisângela Venâncio (2007)
The present research had as objective to establish where moment of the Brazilian scene had the necessity of the foundation of the Movement Athlete of Christ. The analysis of the social context, politician, economic, sporting and religious, in which the Movement was established Athlete of Christ, contributed for the understanding of the nature of the relations between Sport and Religion, in Modernity. This movement of Christians athletes came to play role of mediator between the Fields Religious and Sporting of the time that kept, until then, queerness relations. The theoretical picture is composed for a presentation of the history of the modern sport in occident, centuries XIX and XX. The social theory of Pierre Bourdieu on the analysis of the concepts of Habitus e Field, had based the quarrel of the hypotheses, as for the understanding of the Field Sporting and Religious. The field research was of qualitative nature, with analysis of primary and secondary sources; the collection of data consisted of the participant comment of the periodic meetings of the Movement Athlete of Christ, of the critical reading of 80 certifications of athlete of Christ and of the interviews with athlete and directors of the Movement. By means of the theoretical reference and the research of field, we could verify our hypotheses, answering the two questions that if had shown central offices to this research: the Movement Athlete of Christ was established in the bulge of the process of changes of years 60 that it constituted the Sporting Field and the Religious one; e, the second question, the Movement Athlete of Christ, to the established being, two fields made possible the insertion of Christians athletes in these